A new stem group echinoid from the Triassic of China leads to a revised macroevolutionary history of echinoids during the end-Permian mass extinction. Issue 1 (31st January 2018) - Thompson, Jeffrey R.; Hu, Shi-xue; Zhang, Qi-Yue; Petsios, Elizabeth; Cotton, Laura J.; Huang, Jin-Yuan; Zhou, Chang-yong; Wen, Wen; Bottjer, David J.
Abstract : The Permian–Triassic bottleneck has long been thought to have drastically altered the course of echinoid evolution, with the extinction of the entire echinoid stem group having taken place during the end-Permian mass extinction. The Early Triassic fossil record of echinoids is, however, sparse, and new fossils are paving the way for a revised interpretation of the evolutionary history of echinoids during the Permian–Triassic crisis and Early Mesozoic. A new species of echinoid, Yunnanechinus luopingensis n. sp. recovered from the Middle Triassic (Anisian) Luoping Biota fossil Lagerstätte of South China, displays morphologies that are not characteristic of the echinoid crown group. We have used phylogenetic analyses to further demonstrate that Yunnanechinus is not a member of the echinoid crown group. Thus a clade of stem group echinoids survived into the Middle Triassic, enduring the global crisis that characterized the end-Permian and Early Triassic. Therefore, stem group echinoids did not go extinct during the Palaeozoic, as previously thought, and appear to have coexisted with the echinoid crown group for at least 23 million years. Stem group echinoids thus exhibited the Lazarus effect during the latest Permian and Early Triassic, while crown group echinoids did not.